Peter Daniel Rossdale. (17th December 2021) - Hunt, Michael; Ricketts, Sidney; Digby, Nick Wingfield; Greet, Tim; Carson, Deidre; McGladdery, Andrew; Barrelet, Frederic; Shepherd, Michael; Ramzan, Peter; Payne, Richard; Bathe, Andrew; Cameron, Ian; et al.
Abstract : A dedicated equine clinician and scientist who had varied interests and published widely. He founded a remarkably successful practice and was one of the first to embrace evidence‐based veterinary medicine.